Critical information infrastructures security : 9th International Conference, CRITIS 2014, Limassol, Cyprus, October 13-15, 2014, Revised selected papers /: 9th International Conference, CRITIS 2014, Limassol, Cyprus, October 13-15, 2014, Revised selected papers. (2016) - Unknown
No abstract available